If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) = 4(2x + -1) Reorder the terms: 2(-3 + x) = 4(2x + -1) (-3 * 2 + x * 2) = 4(2x + -1) (-6 + 2x) = 4(2x + -1) Reorder the terms: -6 + 2x = 4(-1 + 2x) -6 + 2x = (-1 * 4 + 2x * 4) -6 + 2x = (-4 + 8x) Solving -6 + 2x = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -6 + 2x + -8x = -4 + 8x + -8x Combine like terms: 2x + -8x = -6x -6 + -6x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 + -6x = -4 + 0 -6 + -6x = -4 Add '6' to each side of the equation. -6 + 6 + -6x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = -4 + 6 -6x = -4 + 6 Combine like terms: -4 + 6 = 2 -6x = 2 Divide each side by '-6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 3x+10=4x+33 | | sin(4*pi*x)+4*pi*x*cos(4*pi*x)=0 | | 4y=5x+5 | | (7rs^5)(-3r^3s^4)=x | | 5b^2+13n+4-7n+9=0 | | 55=2x^2+5 | | 4568931567+245776544223456654324556= | | 4(x+4)=6(2x-2)+12 | | 27/729 | | 7x+4x+8=.027 | | 10+2x=7x-9 | | .7x-1.4=-3.5 | | -4(2t+4)=-24 | | 5904=p(1+0.08*8) | | -8x-5(x+1)=2(x+5) | | (3x-7)(5x+6)=0 | | 6.3x=31.5 | | -7x+4x=-21 | | 10(s-4)=-93 | | 30-37=7x | | 3x-13x=70 | | (-4/11)3= | | x/37 | | 4x=-12+x | | 55=x+4x | | 9/7x9/7x9/7x9/7x9/7x9/7= | | X^3+3X^2+2X-3360=0 | | 8(-13)-9y=50 | | 7-5q=3 | | ln(3x-12)=3 | | a=82*44 | | x-.3x=1610 |